2020
DOI: 10.1242/dev.181297
|View full text |Cite
|
Sign up to set email alerts
|

Integration of luminal pressure and signalling in tissue self-organization

Abstract: Many developmental processes involve the emergence of intercellular fluid-filled lumina. This process of luminogenesis results in a build up of hydrostatic pressure and signalling molecules in the lumen. However, the potential roles of lumina in cellular functions, tissue morphogenesis and patterning have yet to be fully explored. In this Review, we discuss recent findings that describe how pressurized fluid expansion can provide both mechanical and biochemical cues to influence cell proliferation, migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 102 publications
(135 reference statements)
3
39
0
Order By: Relevance
“…For example, smooth muscle cells are not necessary for the initiation of cleft formation (Figure 2D) 50 , but should mechanically assist the cleft formation from the outside of an epithelium, realizing the stable terminal bifurcation 27,50 . Luminal fluid is another potentially important factor that can mechanically affect epithelial tissue deformation through shear stress and hydrostatic pressure 51 . It has been previously reported that the manipulation of luminal pressure in murine developing lungs under ex vivo culture conditions altered branch formation 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, smooth muscle cells are not necessary for the initiation of cleft formation (Figure 2D) 50 , but should mechanically assist the cleft formation from the outside of an epithelium, realizing the stable terminal bifurcation 27,50 . Luminal fluid is another potentially important factor that can mechanically affect epithelial tissue deformation through shear stress and hydrostatic pressure 51 . It has been previously reported that the manipulation of luminal pressure in murine developing lungs under ex vivo culture conditions altered branch formation 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The second term of Equation 5 represents the mechanical effect of luminal pressure 34,35,51 on the apical edge of epithelial cells. The function f was defined as…”
Section: (Iic) Mathematical Modeling For Multicellular Dynamicsmentioning
confidence: 99%
“…In turn, luminal pressure leads to increased cortical tension in the TE and tight junction maturation to allow lumen expansion ( Chan et al, 2019 ). This is a perfect example of how mechanical cues, in this case hydrostatic pressure, affect differentiation ( Chan and Hiiragi, 2020 ).…”
Section: The Implanting Embryo: a Global Transformationmentioning
confidence: 99%
“…The mechanism of luminogenesis has been extensively investigated with 3D-cultured MDCK cells (MDCK: Madin-Derby Canine Kidney cell line) [ 39 ]. The mechanical cues mediated by lumen enlargement and oscillations are also essential during embryo development [ 40 ]. Strikingly, the release of the blastocyst from the zona pellucida is driven by an active swelling and shrinking of the lumen.…”
Section: Discussionmentioning
confidence: 99%